2016
DOI: 10.1002/alr.21843
|View full text |Cite
|
Sign up to set email alerts
|

The pain–depression dyad and the association with sleep dysfunction in chronic rhinosinusitis

Abstract: Background Depression, pain, and sleep disturbance is a symptom cluster often found in patients suffering from chronic illness, exerting a large impact on quality-of-life (QOL). A wealth of literature exists demonstrating a significant association between depression, pain, and sleep dysfunction in other chronic diseases. This relationship has not been described in patients with chronic rhinosinusitis (CRS). Methods Sixty-eight adult patients with CRS were prospectively enrolled. Patients at risk for depressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 39 publications
4
32
0
Order By: Relevance
“…Chronic rhinosinusitis symptoms can have a negative impact on quality of life [47], especially in interference with sleep [65]. Lack of sleep is correlated with depression in CRS patients [3]. In our study, patients experienced better sleep after treatment and reported improvement in overall quality of life.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Chronic rhinosinusitis symptoms can have a negative impact on quality of life [47], especially in interference with sleep [65]. Lack of sleep is correlated with depression in CRS patients [3]. In our study, patients experienced better sleep after treatment and reported improvement in overall quality of life.…”
Section: Discussionsupporting
confidence: 49%
“…Current research suggests that CRS is predominantly an inflammatory disease, with current therapies targeting inflammation within the sino-nasal cavity [2]. Symptoms of nasal congestion and facial pain significantly reduce the quality of life of CRS patients [3,4]. Many patients continue to experience pain after both medical and surgical management.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is important, as the relationship between the SNOT-22 score (a condition-specific instrument) and other specific instruments designed to be sensitive to depression and pain, was previously unclear. These are important domains which have been previously reported to be inadequately measured by the SNOT-22 [21], though the effects of which have been suggested elsewhere [11, 13]. …”
Section: Discussionmentioning
confidence: 99%
“…Sino-nasal symptoms have been documented to be associated with significant anxiety and depression [10, 11]; especially in patients without polyps [11], and more than half of patients with CRS reportedly suffer from pain [12, 13]. Dysfunction of sleep and pain have been seen to be inter-related in the presence of depression [13]. However, very little is known about the health status of those patients with CRS on the wait list for ESS, representing a significant knowledge gap that can impair clinical decision making.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, positive correlations were found between pain measures and total PSQI score or the 3 PSQI subdomains that measure sleep latency, sleep quality, and daytime dysfunction (all p values < 0.05). Interestingly, the link between sleep dysfunction and pain was limited to CRS patients who were at risk for depression, indicative of the clustering of these major symptoms in CRS [29]. …”
Section: Importance and Relevance Of Sleep Disruption In Crsmentioning
confidence: 99%